2021
DOI: 10.1177/1077801221996463
|View full text |Cite
|
Sign up to set email alerts
|

“If You Are Born a Girl in This Crisis, You Are Born a Problem”: Patterns and Drivers of Violence Against Women and Girls in Conflict-Affected South Sudan

Abstract: This article presents the results of a qualitative study on the context and different forms of violence committed against women and girls in South Sudan. The study documents many forms of sexual and physical violence against women and girls in South Sudan, including conflict-related sexual violence, intimate partner violence, nonpartner sexual violence, child and forced marriage, and abduction. Violence occurred during three overarching contexts: armed conflict, gender inequality, and the economic crisis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
(38 reference statements)
3
21
0
1
Order By: Relevance
“…Feminist researchers posit that the root causes of VAWG, in both conflict and nonconflict settings, are unequal gender dynamics and patriarchal norms and practices that discriminate against women and girls. Research in nonconflict affected settings has demonstrated this connection between gender inequality and rates of IPV (Heise & Kotsadam, 2015), and some researchers have suggested these inequalities may contribute to increases in the utilization of conflict-related sexual violence as a facet of warfare (Coulter, 2009; Ellsberg et al, 2021; Olujic, 1998). However, the exact connection between gender inequality and conflict-related sexual violence is unclear, and cross-national analysis did not find gender inequality to be associated with higher rates of wartime rape (Cohen, 2013).…”
Section: Overview Of the Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Feminist researchers posit that the root causes of VAWG, in both conflict and nonconflict settings, are unequal gender dynamics and patriarchal norms and practices that discriminate against women and girls. Research in nonconflict affected settings has demonstrated this connection between gender inequality and rates of IPV (Heise & Kotsadam, 2015), and some researchers have suggested these inequalities may contribute to increases in the utilization of conflict-related sexual violence as a facet of warfare (Coulter, 2009; Ellsberg et al, 2021; Olujic, 1998). However, the exact connection between gender inequality and conflict-related sexual violence is unclear, and cross-national analysis did not find gender inequality to be associated with higher rates of wartime rape (Cohen, 2013).…”
Section: Overview Of the Modelmentioning
confidence: 99%
“…In conflict-affected settings, weak states may experience more sexual violence by rebel groups during civil wars (Cohen, 2013). These weak or failing states are often unable to fulfill their roles as purveyors of justice, enabling multiple forms of CRVAWG (Ellsberg et al, 2021; Goetze, 2008). Informal institutions, customary justice processes, or traditional and religious leadership structures may step in where formal state structures fail.…”
Section: Overview Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has also documented the impact of political conflict on the level of DV/IPV in the majority and/or minority populations (Doyle and McWilliams, 2020), noting the risk of community violence toward women and their children in mixed relationships during flare-ups of inter-group conflict (Ellsberg et al, 2021; Hartley, 2010). Prior studies have also identified unique DV/IPV risk factors associated with political conflict and documented how exposure to conflict affects or magnifies risk factors (e.g.…”
Section: Introduction and Theoretical Frameworkmentioning
confidence: 99%